Checklist application to evaluate good management practices in aquaculture (Research, Society and Development, 2021)
The objective of the study was to evaluate good management practices through a Checklist for aquaculture enterprises in the Marajó archipelago (Pará, Brazil). The research was carried out in the municipality of Curralinho, as part of the actions of the project “Transfer of technology through training and technical assistance for creators of tambaqui, Colossoma macropomum, in the archipelago of Marajó/PA” of the Federal Institute of the Pará (IFPA), Campus Breves, between September 2019 and January 2020. A total of 13 fish farms participated in the survey. The instrument for data collection was a checklist, which includes items related to the management of fish farming. After applying the checklist, it was possible to identify that the implementation of fish farming, identification of infrastructure, soil management and application of limestone, occurrence of diseases and storage of fry, presented levels of non-conformities between 75% to 79%. The items filters and anti-leak prevention, handling during the process of draining the tanks, stocking density and handling of fishing, presented levels of non-conformities between 80 - 89%. For the item soil disinfection the level of non-conformities was 94% and for the items: fertilization, protection of tanks with anti-bird nets, water quality, biometrics management, transfer management, cleaning procedures and equipment asepsis and the condition and safety of fish farming workers, presented levels of non-conformities varying between 95 - 100%. It was concluded that all sites are not suitable for good practices and therefore put the species' fish farming in the region at risk.